An ethnomathematical analysis of the Gandrung Lombok dance as an effort to utilize local wisdom in the mathematics learning process - Hidayati, Djuita; Anggraini , Erna; Suryadmaja, Galih (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2024)
Ethnomathematics is currently also a bridge for the emergence of new strategies in the mathematics learning process. The aim is to make mathematics easier to understand by finding cultural facts in everyday life, such as in the Gandrung Lombok dance. Until now, there has been no study of ethnomathematical analysis of the various movements of the Gandrung Lombok dance that can be used in the learning process. This research aims to explain the ethnomathematics aspects of various Gandrung Lombok dance movements. The research used a qualitative descriptive method with an ethnographic approach involving participant observation, interviews, and documentation. Interviews were conducted with maestros and performers to explain and describe various mathematical phenomena in various Gandrung Lombok dance movements. Then, the collected field data was analyzed using a qualitative descriptive approach, and the validity of the data used in this research was tested using triangulation techniques. The research results explain that counting and measuring activities are performed in various Gandrung Lombok movements. Counting activities are carried out repeatedly by counting the numbers one to eight accompanied by accompanying music. Measurement activities in the presentation of Gandrung Lombok dance movements are implemented in the presentation of movement patterns, including hand, foot, and floor patterns. Ethnomathematics related to measurement is carried out by applying the geometric concepts of semicircles, circles, and triangles. The triangle concept is the most dominant concept in various Gandrung Lombok movements, which can be seen in the shape of the hand and foot patterns. One of the findings in this research explains that the concept of triangular geometry is an important element in building the aesthetic image of Gandrung Lombok, which needs further proof.